Environmental risk indicators disclosure and value relevance: An empirical analysis of Italian listed companies after the implementation of the Legislative Decree 254/2016. (29th July 2021) - Paolone, Francesco; Granà, Fabrizio; Martiniello, Laura; Tiscini, Riccardo
Abstract: In response to EU Directive 95/2014, many companies headquartered in Europe have strengthened their non‐financial disclosure on environmental strategies and risks. In particular, the Directive was applied by Italian law, with the Legislative Decree 254/2016, requiring the largest Italian companies (exceeding 500 employees) to provide detailed information on their social and environmental disclosures. In this paper, we aim to analyze the value relevance of financial and environmental information provided by the Italian, non‐financial listed companies after the implementation of the Legislative Decree 254/2016. By building on the signaling theory, we set a pooled regression analysis to test the relationship between environmental disclosure and value relevance for the period 2017–2018. We contribute to the literature by arguing that Italian companies' market value depends on both their financial and environmental disclosures. More specifically, we argue that accounting information is not sufficiently capable to explain the value relevance and it needs to be integrated by a set of environmental information. Our contribution aims at demonstrating that the higher the levels of environmental risk indicators disclosure, the greater a company's market performance.